Pengaruh Lama Penyimpanan Nira Kental Sulfitasi Terhadap Karakteristik Nira Pada Proses Produksi Gula - Aryani, Arisma Dila; Irawan, Tofan Andrew; Putri, Desiana Nuriza; Harini, Noor (Universitas Veteran Bangun Nusantara, 2023)
Sulfated Condensed Nira is sugarcane juice that has undergone several production processes ranging from milling and purification to evaporation and has been mixed with other substances such as lime/sulfur. One of the problems encountered in Indonesian sugar factories is the waiting time for the thick sulfate juice in the crate of thick sap before the cooking process is carried out. This is caused by several things, such as damage to the production machine, overcapacity cooking process, and mill wash. This study aimed to determine the effect of extended storage of sulfate viscous sap on the characteristics of the sap produced in the production process of white crystalline sugar. It uses a sample of thick sulfate sap taken in a crate of thick sap with five treatments, namely storage time of 0 hours, 2 hours, 4 hours, 6 hours, and 8 hours. Parameters tested include total dissolved solids (% Brix), sugar content, pH, color, and turbidity. The results showed that the storage of concentrated sulfate juice significantly affected %Brix. At 0 hours to 4 hours of storage, it increased and decreased after 6 hours. The sugar content in the thick sulfated sap increased at 0 to 4 hours of storage and decreased after 6 hours. Increasing the sugar content in sap is caused by the decomposition of polysaccharides into sugars (sucrose, glucose, and fructose), and the decrease in sugar content is caused by fermentation by Saccharomyces. The storage time of 0 hours was significantly different from the storage time of 2 hours, 4 hours, 6 hours, and 8 hours on the pH of the sulfitation thick juice due to the addition of lime milk to keep the pH of the juice high and prevent hydrolysis either by microbes or acids. The longer the storage, the darker and more cloudy the resulting color.